Oltre i margini: comunità, risorse, prospettive - Laura Bonato; Damiano Cortese; Roberta Clara Zanini (EtnoAntropologia)
Making use of the ethnographic observation that the UR of Turin is carrying out as part of the Prin 2020 project on four localities in the Piedmontese Alps, an attempt will be made to analyse the presence of community planning and awareness of the cultural and social meanings of their actions with a view to producing meaning and culture. While these inland, marginal areas are still characterised by forms of depopulation, this situation can generate new practices for a more balanced and sustainable growth. This is a significant ‘growth potential’ still to be discovered through related strategic elements such as the environment, culture, agriculture, renewable energy and tourism, in order to enable a suitable economic development of local communities through the preservation of agro-cultural landscapes and historical-artistic heritage.